Hybrid Deep Eutectic Solvent of LiTFSI-Ethylene Glycol Organic Electrolyte for Activated Carbon-Based Supercapacitors - Kieu T. Tran; Tuyen T. T. Truong; Hoang V. Nguyen; Quan D. Nguyen; Quan Phung; Phung M. L. Le; Man V. Tran (Journal of Chemistry)
This research work demonstrates a novel hybrid electrolyte based on a deep eutectic solvent (DES) combined with organic solvents for high-performance supercapacitors. DES was formed between ethylene glycol (EG) and lithium bis((trifluoromethyl)sulfonyl) imide (LiTFSI) and diluted by ethylene carbonate (EC) or acetonitrile (AN) with different amounts (10–50% wt.). Such a combination gives superior properties for hybrid electrolytes compared to pure DESs and reduces the volatility of mixed organic solvents. Regarding the electrochemical properties, DES-AN mixtures exhibited a better performance under high applied voltage and more reversible behavior than DES-EC ones, which suffered from the increasing distance in the electrical double layer. DES 1 : 4 + 20% wt. AN exhibited favorable electrolyte properties such as high ionic conductivity (3.1 mS·cm−1 at 30oC), relatively lower viscosity (14.28 mPa s at 30oC, approximately 2 times lower thanDES pure), and quite large electrochemical stability window up to 3.4 V (at 20–30% wt. AN) compared to the baseline electrolyte (LiTFSI/TBABF4 in AN). With these interesting properties, selected hybrid electrolyte (DES 1 : 4 + 20% wt. AN) tested in the symmetric capacitor using the activated carbon offered decent capacitance (15 F·g−1 at 3.4 V with a scanning rate of 1 A·g−1 and remains around 95% after 100 cycles) and good charge-discharge durability (>80% retention after 2000 cycles), especially the EDLC with DES 1 : 4 + 20% wt. AN shows good rate capacity (13.2 F·g−1 at 2 A·g−1, remaining 6 F·g−1 at 10 A·g−1).